Comparison of Hip Abductor and Adductor Muscle Strength in Taekwondo and Non-taekwondo Practitioners - Seet Jia Sheng; Fachry Ambia Tandjung; Marietta Shanti Prananta (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Taekwondo is an empty hand combat that entails the use of the whole body. Spinning and turning kicks are the proper way of kicking in taekwondo which allow one to maximally perform the hip abductor and adductor muscles simultaneously. To measure the hip abductor and adductor muscles of Taekwondo and Non-taekwondo practitioners, Hand-Held Dynamometer (HHD) is used. This study aimed to compare the hip abductor and adductor muscles strength in Taekwondo and Non-taekwondo practitioners.Methods: This analytical study of paired continuous variable was conducted using cross-sectional method. Thirty-two subjects were examined from September−October 2014 at the skills laboratory of Faculty of Medicine, Universitas Padjadjaran. Sixteen of them were Taekwondo practitioner and the other sixteen of them were Non-Taekwondo practitioner. Gender, weight, height, Body Mass Index (BMI) and maximum strength of hip abductor and adductor muscles were examined by using Hand-Held Dynamometer (HHD).Results: Off all physical characteristics being examined, it showed that the p-values were above 0.5. The independent t-test showed that the average strength of hip abductors and adductors muscle in Taekwondo and Non-taekwondo practitioners were significantly different in which the both p-values were less than 0.05.Conclusions: The maximum strength of hip abductor and adductor muscles of Taekwondo and Non-taekwondo practitioners were significantly different. The strength of hip abductors and adductors muscles is greater in Taekwondo practitioners compared to Non-taekwondo practitioners. [AMJ.2016;3(3):392–5]DOI: 10.15850/amj.v3n3.886